1978
DOI: 10.1161/01.res.43.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Subpressor angiotensin infusion, renal sodium handling, and salt-induced hypertension in the dog.

Abstract: SUMMARY We studied the combined effect of subpressor amounts of angiotensin and long-term sodium chloride infusion on arterial pressure in 16 dogs for periods of 2-8 weeks. In dogs receiving 3.5 liters of isotonic NaCl daily, but no angiotensin, the arterial pressure increased an average of only 3 mm Hg. When angiotensin was infused continuously at a rate of 5 ng/kg per min (a rate too small to cause an observable immediate increase in pressure), subsequent infusion of 3.5 liters of saline daily then increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 33 publications
(27 reference statements)
5
71
1
1
Order By: Relevance
“…Previous experiments have demonstrated that hypertension associated with systemic ANG II administration is enhanced with concurrent administration of increased dietary sodium (1,8,9). Although not directly tested in all of these earlier studies, the data are consistent with increased SNS tone contributing to the increase in blood pressure (7).…”
Section: Discussionmentioning
confidence: 69%
“…Previous experiments have demonstrated that hypertension associated with systemic ANG II administration is enhanced with concurrent administration of increased dietary sodium (1,8,9). Although not directly tested in all of these earlier studies, the data are consistent with increased SNS tone contributing to the increase in blood pressure (7).…”
Section: Discussionmentioning
confidence: 69%
“…For example, several studies show that long-term infusion of angiotensin II (ANG II) causes salt-dependent hypertension in experimental animals (1,7,9,11,12,16). However, the precise nature of the relationship between plasma ANG II and long-term salt sensitivity of arterial pressure remains unclear.…”
mentioning
confidence: 99%
“…This assumption has led us to suggest that the circulating levels of angiotensin are inappropriate or in excess when compared with the level of extracellular fluid volume. This hypothesis is largely supported by the studies of DeClue et al (52) who showed that when sodium intake is increased without allowing the circulating levels of angiotensin to be decreased because of continuous intravenous infusion, then the levels of blood pressure become strictly determined by the level of sodium intake. The observations of DeClue et al (52) have many physiological and clinical implications.…”
Section: Isoprostanesmentioning
confidence: 89%